Master Data Management Model in Company: Challenges and Opportunity - Indrajani, Indrajani (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The purpose of this research is to analyze, design, and implement Master Data Management (MDM) model for company, which include database processing that will be used in the quality of data customer and produce single view of customer. The research method used is literature study from a variety of journals, books, e-books, and articles on the internet. Also, fact finding techniques are done, such as by analyze, collect, and examine the documents, interviews, and observations. Then, other research methods used to analyze and design MDM model are using cleansing and matching technique. The result obtained from this research is animplementation MDM model for the company, where if implemented, will improve the quality of data significantly. The conclusion which can be obtained from this research is that MDM is one of the factors thatcan improve the quality of customer data.